Examination of Technology in Turkish Social Studies Curricula - ÖZTÜRK, CEMİL (ELSEVIER SCIENCE BV, 2012)
This study is designed in descriptive model because it aims to analyze 4th, 5th, 6th and 7th grade social studies curricula in a technology focused view. In this context, document analysis technique was used which is a qualitative research method. Learning areas, acquisitions and skills in social studies curricula are considered in evaluation process. In conclusion, it was seen that in social studies curricula, Science, Technology and Society learning is directly technology oriented and this learning area has strict connections with others. Technology oriented activities are also implemented as needed in other learning areas. Besides, it was determined that there are 23 technology oriented acquisitions in 4 th, 5 th, 6 th and 7 th grade social studies curricula in Turkey. Six of them are in the 4th grade, six of them are in the 5th grade, five of them are in the 6th grade and six of them in the 7th grade. In this context, technology oriented acquisitions formed 13,2% of whole acquisitions in curricula (total 174). In skill dimension using information technologies skill is technology oriented and it is towards the effective usage of technology. (C) 2012 Published by Elsevier Ltd. Selection and/or peer-review under responsibility of The Association Science Education and Technology
Keywords: Social studies; curriculum; technology; technology literacy; EDUCATION; SCIENCE; DESIGN